Vozes em diálogo em documentos que tematizam a interiorização da UFPA - AZEVÊDO, Maria da Conceição (Universidade Federal do Pará, 2020)
We aimed to identify elements to describe legitimate partners in the implementation of the Federal University of Pará education policy in the interior of the state by analyzing official documents issued during the beginning of the process in the mid-1980s.We intend to retrieve the partners’ voices in the construction of Federal University of Pará at a crucial time of its history. Questions addressed include: Who are Federal University of Pará’s actual partners in the implementation of its policy?; Are they its management staff, its faculty members, the Amazonian communities, the municipalities, or the federal government of the brand new republic?; Whose are those voices and how do they echo in the documents that witnessed the beginning of the referred policy? We are grounded in notions of voices, production context (BRONCKART, 1999) and discourse genres (BAKHTIN, 2003). Two documents comprise the corpus: official documents related to the institucional policy. We analyzed how the different voices interact in enunciative texture in order to identify to what extent and in what ways the instances of enunciation can categorize the policy that allowed the expansion for this university into the state.